2018
DOI: 10.22354/in.v22i4.741
|View full text |Cite
|
Sign up to set email alerts
|

Leclercia adecarboxylata, a rare cause of soft tissue infections in immunocompromised patients, case report and review of the literatura

Abstract: Leclercia adecarboxylata is a member of the Enterobacteriaceae family that has been isolated from several environmental and animal specimens, however it rarely causes diseases in human beings. It has natural resistance to several antibiotics, and has shown the ability to harbor and produce enzymes capable of hydrolyzing most of the antibiotics used in daily clinical practice, making its treatment a challenge when a strain with such characteristics causes disease. Here we report the first known case of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the literature, patients with L. adecarboxylata infection usually also have severe immunosuppression, for example, through the use of immunomodulators or chemotherapy [ 7 , 22 , 23 ]. On the other hand, few cases with diabetes as the only risk factor had skin and soft tissue infection [ 24 , 25 ]. Our patient had a PICC line for a few days, which could have been the source; however, only a peripheral blood culture was positive, contradicting this theory.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, patients with L. adecarboxylata infection usually also have severe immunosuppression, for example, through the use of immunomodulators or chemotherapy [ 7 , 22 , 23 ]. On the other hand, few cases with diabetes as the only risk factor had skin and soft tissue infection [ 24 , 25 ]. Our patient had a PICC line for a few days, which could have been the source; however, only a peripheral blood culture was positive, contradicting this theory.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, increasing resistance to these antibiotic agents has been reported in the literature. 4,5 L. adecarboxylata has a very similar microbiological appearance to Escherichia coli, a common microbial pathogen. It has been theorized that L. adecarboxylata infections have been underreported due to the similarities with E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…However, a cumulative report of human infections by L. adecarboxylata mostly in immunocompromised patients suggested that the organism is an opportunistic bacterium and the infections caused by it are underestimated. It has been reported to cause septicemia [5], wound infection [6,7], urinary tract infection [8,9], posttraumatic polymicrobial infection [10], soft tissue infection [11], and peritonitis [12]. e majority of clinical isolates of L. adecarboxylata were susceptible to commonly used antibiotics [4], and multidrug-resistant isolates have rarely been reported [8].…”
Section: Introductionmentioning
confidence: 99%